OCCUPATIONAL SEGREGATION AND LABOUR FORCE PARTICIPATION OF WOMEN: CASE OF NORTH CYPRUS - Kalmaz, Demet Beton; Lisaniler, Fatma Güven (My University, 2019)
Previous studies on North Cyprus labour market argued that occupational gendersegregation is one of the major cause of low female labour force participation. Weaim to shed light on this argument by investigating the extent, patterns and thesources of occupational gender segregation in North Cyprus labour market for 11years (2004-2014). Segregation measured by D-Index for 9 broad occupationalcategories for total, and across rural and urban regions employing HouseholdEmployment Surveys data. Results show that total occupational gendersegregation is high and persistent in North Cyprus. Decomposition of the indexshow that the main reason for the increase in segregation level is net segregation;the increase in the gender composition of individual occupations. We concludethat high and persistent occupational gender segregation leads to thesegmentation of labour market as male and female occupations limiting themobility of women between occupations affecting women’s labour forceparticipation negatively.
Keywords: Kadın Araştırmaları; İktisat